Eye tracking in MSN Search: Investigating snippet length, target position and task types - Cutrell, Ed; Guan, Zhiwei (2007)
Web search services are among the most heavily used applications on the World Wide Web. Perhaps because search is used in such a huge variety of tasks and contexts, the user interface must strike a careful balance to meet all user needs. We describe a study that used eye tracking methodologies to explore the effects of changes in the presentation of search results. We found that adding information to the contextual snippet significantly improved performance for informational tasks but degraded performance for navigational tasks. We discuss possible reasons for this difference and the design implications for the better presentation of search results. The studies reported here are to be published in CHI 2007.